Knock-down of PRAME increases retinoic acid signaling and cytotoxic drug sensitivity of Hodgkin lymphoma cells. - Stefanie Kewitz; Martin S Staege (PLoS ONE, 2013)
The prognosis for patients with Hodgkin lymphoma (HL) has improved in recent decades. On the other hand, not all patients can be cured with the currently established therapy regimes and this therapy is associated with several adverse late effects. Therefore it is necessary to develop new therapy strategies. After treatment of L-540 HL cells with 5'-azacytidine (5AC), we observed increased expression of the preferentially expressed antigen in melanoma (PRAME). In addition, we detected an increased resistance of 5AC-treated cells against cytotoxic drugs. We analyzed the influence of PRAME on cell survival of HL cells by knocking down PRAME in the chemotherapy resistant cell line L-428, a cell line that express PRAME at a high level. After knock-down of PRAME using vector based RNA interference we observed increased sensitivity for cisplatin, etoposide and retinoic acid. DNA microarray analysis of HL cells after PRAME knock-down indicated regulation of several genes including down-regulation of known anti-apoptotic factors. Increased retinoic acid signaling in these cells was revealed by increased expression of the retinoic acid metabolizing cytochrome P450 (CYP26B1), a transcriptional target of retinoic acid signaling. Our data suggest that PRAME inhibits retinoic acid signaling in HL cells and that the knock-down of PRAME might be an interesting option for the development of new therapy strategies for patients with chemo-resistant HL.